The Effect of Oil Prices, Gold and Exchanges on JCI During the Covid-19 - Sri Wahyuni Lubis; Mohamad Fany Alfarisi; Fajri Adrianto (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of changes in crude oil prices, gold prices, and exchange rates on the volatility of the Composite Stock Price Index (JCI) during the Covid-19 pandemic. Using quantitative methods with descriptive research typeswith composite stock price index (CSPI) data, crude oil price data (WTI), gold price data (London Gold) and data on the Rupiah exchange rate against the Dollar during the Covid-19 pandemic starting from 02 March 2020 to 25 March 2021 taken from Datastream at Eikon Faculty of Economics, Andalas University, Padang and obtained 275 samples. The results of the study using the Arch/Garch method found that there was no significant effect between the price of Crude Oil on the JCI, while for the price of Gold there was a significant positive effect on the JCI and for the exchange rate there was no significant effect on the JCI. The results of the ARIMA forecasting method until March 25, 2022 found that the JCI tends to increase, as seen from the second quarter of 2021 (beginning of forecasting) to the first quarter of 2022, the JCI continues to move up. Crude Oil Prices have decreased until the first quarter of March 2022, Gold prices tend to be stable with not too many significant changes. Meanwhile, the Rupiah Exchange Rate against the US Dollar experienced an appreciation, moving up until the end of the forecast in the first quarter of 2022.